2015
DOI: 10.13066/kspm.2015.10.3.87
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of lower extremity strength, cognition, and ankle mobility according to the 8.5seconds cut-off point for the 8-foot up-and-go test in elderly women

Abstract: The purpose of this study was to investigate the effects of the 8.5seconds cut-off of the 8-foot up-and-go test as a predictor of falling and a good discriminator of fallers and non-fallers in women in their 60s to 80s. METHODS:The final subjects of this study were 98 elderly women from six senior centers of B metropolitan city.The 8-foot up-and-go test evaluated agility and dynamic balance. The chair-stand test measured the muscle strength for of the lower body. Ankle dorsiflexion and plantar flexion were mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
(27 reference statements)
0
5
0
Order By: Relevance
“…The 8-foot up-and-go test is not only a measurement of dynamic balance, agility, and speed but also a good predictor of falling for older adults [ 30 ]. To the best of our knowledge, this is the first study to report that current smoking is negatively associated with 8-foot up-and-go and one-leg stance with eyes open performance in older adults.…”
Section: Discussionmentioning
confidence: 99%
“…The 8-foot up-and-go test is not only a measurement of dynamic balance, agility, and speed but also a good predictor of falling for older adults [ 30 ]. To the best of our knowledge, this is the first study to report that current smoking is negatively associated with 8-foot up-and-go and one-leg stance with eyes open performance in older adults.…”
Section: Discussionmentioning
confidence: 99%
“…The limitation of dorsiflexion leads to major changes in joint arthrokinematics, as talus position and gliding restriction ( 23 ). Kang et al ( 24 ) have reported these changes to be the major causes of gait deviations; reduced stride length, decreased gait velocity, and risk of falls. Improved stride length and gait velocity in this study indicate increased activity of the TA during stance and swing phases of gait.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, it has been reported that the ability to control posture causing compensatory movement of the hip joint and trunk is reduced [22]. In particular, the limitation of dorsiflexion is manifested by changes in joint motion such as talus position and gliding restriction [23,24]; it is one of the major causes of gait disturbance [25] and increased risk of reduced stride, decreased gait speed, and risk of falls [26].…”
Section: Discussionmentioning
confidence: 99%